2018
DOI: 10.1002/jbm.b.34072
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotriphosphate associated to fluoride increases hydroxyapatite resistance to acid attack

Abstract: This study evaluated the effect of sodium trimetaphosphate (TMP) associated or not with fluoride (F) on the structure and dissolution of carbonated hydroxyapatite (CHA). Synthetic CHA powder (1.0 g) was suspended in solutions containing TMP at 0-10%, associated with 0, 1100, 4500, or 9000 ppm F, and the precipitates were submitted to a pH cycle (n = 6/group). Samples were analyzed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction. F, calcium (Ca) and phosphorous (P) concentrations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
(127 reference statements)
2
15
0
Order By: Relevance
“…Those concentrations were based on previous studies that showed the effect of two low‐fluoride dentifrices against tooth erosion containing: 250 ppm F in combination with 0.25% TMP (22) and 500 ppm F in combination with 3% TMP (21). Studies have shown that TMP is capable of binding to the dental substrate through hydroxyl (27) and/or amino sites and this induces the precipitation of calcium phosphate apatite (23, 24), when combined with fluoride in the ratio used in the present study (21, 22, 27). In the present study, cross‐sectional hardness profiles confirmed these data up to 180 µ m depth in the enamel (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Those concentrations were based on previous studies that showed the effect of two low‐fluoride dentifrices against tooth erosion containing: 250 ppm F in combination with 0.25% TMP (22) and 500 ppm F in combination with 3% TMP (21). Studies have shown that TMP is capable of binding to the dental substrate through hydroxyl (27) and/or amino sites and this induces the precipitation of calcium phosphate apatite (23, 24), when combined with fluoride in the ratio used in the present study (21, 22, 27). In the present study, cross‐sectional hardness profiles confirmed these data up to 180 µ m depth in the enamel (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The present study evaluated if the addition of TMP and NaF at two different concentrations to 10% H 2 O 2 bleaching gels would inhibit the enamel demineralization and thereby minimize enamel alterations and consequently decrease tooth sensitivity. It is important to mention that when TMP is not combined with fluoride, it does not lead to a significant reduction in enamel demineralization (26, 27). Thus, the present study tested the ability of the compound formed by the combination of TMP with NaF at different concentrations to reduce the enamel demineralization resulting from the by‐products of H 2 O 2 application.…”
Section: Discussionmentioning
confidence: 99%
“…TMP is adsorbed on the dentin surface, mainly by the amino and hydroxyl groups of collagen [Leone et al, 2008] and hydroxyapatite [Delbem et al, 2014;Amaral et al, 2018], respectively. As is a cyclophosphate, it produces a negative polarity of the surface increases [Neves et al, 2018], enhancing the deposition of calcium phosphate apatite [Favretto et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sodium trimetaphosphate (TMP) is an inorganic phosphate which, when added to fluoride varnishes, reduces enamel erosion by at least 50% compared to the effect of other formulations that contain the same fluoride concentration Manarelli et al, 2014]. TMP has the ability to adsorb on enamel through hydroxyl sites [Delbem et al, 2014;Amaral et al, 2018], thus enhancing the effects of the varnish against enamel erosion [Manarelli et al, 2013;Moretto et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The data show that TMP gets adsorbed by enamel (Fig. 1d) even though both are negatively charged through the interaction between the anionic sites of TMP and hydroxyapatite hydroxyl groups [Delbem et al, 2014;Amaral et al, 2018]. Consequently, enamel surfaces acquire more electron donor sites through TMP adsorption (Fig.…”
Section: Abmentioning
confidence: 99%